(untitled) (Journal of Atomic and Molecular Sciences, 2016)
In this paper, we introduce a new way to obtain the emission spectrum of single molecule driven by external field. A virtual probe field is introduced to simulate the vacuum field, which causes the spontaneous emission phenomena of the excited single molecule. The statistical properties of the emission photons caused by the virtual probe field could be used to obtain the emission spectrum of the single molecule system. The results demonstrate the well-known Mollow triplet splitting phenomenon as the single molecule is driven by strong external field.The abstract should provide a brief summary of the main findings of the paper.